Computed Tomography Perfusion Alberta Stroke Program Early Computed Tomography Score Is Associated with Hemorrhagic Transformation after Acute Cardioembolic Stroke - Liu, Lan; Wu, Bo; Zhao, Jinglong; Cao, Yanyan; Dedhia, Nikita; Caplan, Louis R.; Wang, Qiaoshu (Frontiers in Neurology, 2017)
Alberta Stroke Program Early CT score (ASPECTS) has been applied to CT perfusion (CTP) with good interater agreement to predict early ischemic stroke, and it can be useful in decision making in acute ischemic stroke. The aim of the present study was to assess the predictive value of CTP ASPECTS scores of hemorrhagic transformation (HT) in acute cardioembolic stroke. This is a single-enter, retrospective study. All patients hospitalized with acute cardioembolic stroke from January 2008 to September 2013 were included. ASPECTS scores of baseline noncontrast CT (NCCT), CTP maps of cerebral blood volume (CBV), cerebral blood flow (CBF), and mean transit time (MTT) were collected from 52 consecutive patients with less than 12-hour anterior circulation ischemic stroke. MRI scan was performed within 72 hours of symptom onset after index stroke including T2*-weighted gradient echo (GRE) to identify HT. For bleeding risk assessment, CTP and DWI ASPECTS scores were categorized into 0 to 7 or 8 to 10. Baseline characteristics, ASPCETS scores and HT were compared. Eighteen (34.6%) patients had HT and four (7.7%) developed symptomatic HT. On univariate analysis, the proportion of patients with CBV-ASPECTS scores 0-7 was significantly higher in HT patients as compared to patients without HT (44% versus 9%, P=0.005). CBV ASPECTS score 0-7 remained independent prognostic factors for HT after adjustment for clinical baseline variables. CBV ASPECTS could be of value to predict HT risk after acute cardioembolic stroke and may be a quick risk assessment approach before reperfusion therapy.